1987
DOI: 10.1128/mcb.7.1.167
|View full text |Cite
|
Sign up to set email alerts
|

The membrane-associated enzyme phosphatidylserine synthase is regulated at the level of mRNA abundance.

Abstract: To precisely define the functional sequence of the CHOI gene from Saccharomyces cerevisiae, encoding the regulated membrane-associated enzyme phosphatidylserine synthase (PSS), we subcloned the originai 4.5-kilobase (kb) CHOI clone. In this report a 2.8-kb subclone was shown to complement the ethanolamine-choline auxotrophy and to repair the defect in the synthesis of phosphatidylserine, both of which are characteristic of chol mutants. When this subclone was used as a hybridization probe of Northern and slot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
112
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 53 publications
6
112
0
Order By: Relevance
“…Not only was the degree of repression of certain genes enhanced but also a greater number of genes were found to be differentially expressed in the presence of both precursors. This is in agreement with previous reports measuring expression of individual genes, including INO1 (16), CHO1 (17,20), OP13 (21), CKI1 (52). We also show for the first time that ITR1, YEL073C, YIP3, PSD1, and SAH1 match this pattern of regulation.…”
Section: Analysis Of Genome-wide Expression Regulated By Inositolsupporting
confidence: 93%
See 2 more Smart Citations
“…Not only was the degree of repression of certain genes enhanced but also a greater number of genes were found to be differentially expressed in the presence of both precursors. This is in agreement with previous reports measuring expression of individual genes, including INO1 (16), CHO1 (17,20), OP13 (21), CKI1 (52). We also show for the first time that ITR1, YEL073C, YIP3, PSD1, and SAH1 match this pattern of regulation.…”
Section: Analysis Of Genome-wide Expression Regulated By Inositolsupporting
confidence: 93%
“…For example, it was originally reported that INO1 expression is repressed by an additional 2-3-fold in cells grown in inositol-containing medium when choline is present compared with cells grown in inositol-containing medium when choline is absent (16). Similar simultaneous effects of inositol and choline have also been observed for CHO1 (17,20), OP13 (21), CHO2 (21), CKI1 (52), and CPT1 (53). All of the above genes have been shown to contain an active UAS INO element in their promoters, suggesting that the additive repressive effect of choline in the presence of inositol might be specific to this particular set of genes.…”
Section: Global Analysis Of Inositol and Choline On Gene Expressionmentioning
confidence: 56%
See 1 more Smart Citation
“…CHO1 expression is regulated by water-soluble phospholipid precursors (e.g. inositol supplementation) (59,90,94,95) and by growth phase (96,97). The activity of PS synthase is modulated by membrane phospholipids (98 -100) and is inhibited by inositol (101) and by CTP (39).…”
Section: Discussionmentioning
confidence: 99%
“…Inositol is a key regulator of the enzymes required for inositol and phospholipid biosynthesis. Regulation of many of these enzymes by inositol occurs at the level of transcript abundance (Bailis et al, 1987;White et al, 1991). The products of three regulatory genes bring about inositol-mediated regulation, including the positive regulators INO2 and INO4 and the negative regulator OPI1 (Klig et al, 1988;Nikoloff et al, 1992).…”
Section: Discussionmentioning
confidence: 99%